Dissemination of contextual information for assisted driving - Pereira, João Pedro Ferreira e (2020)
Driver assistance systems can be used to improve road and car safety, reduce driving fatigue and provide a more e cient driving experience. An important part of these systems is the communication between vehicles, and vehicle-to-infrastructure communication. This work presents mechanisms enabling driving support, exploring the vehicular network to provide information about the drivers neighborhood. The network is composed by vehicles, tra c signals and xed stations along the road. Each car is equipped with a recording camera, a GPS receiver, as well as communication modules such as WiFi, WAVE and 3G/4G, allowing the exchange of data between the various nodes. The data exchanged is composed by positional data of neighboring vehicles, sensor information from tra c signals and video images incoming from other vehicles. This data is used to facilitate the driver in decision making, but can also provide an overview of the tra c density in the neighborhood. The tra c signals broadcast their position and if they are dynamic (such as tra c lights), their status is also transmitted. The xed stations are equipped with numerous sensors and are used to provide environmental data. The driver can access all the collected data via visual information, on a display screen that contains a map of the neighborhood along with the information available of the nearby nodes. The proposed system is evaluated through real vehicular experiments in two distinct scenarios: urban and highway. The results show that the communication delay is higher in the highway scenario, mainly due to the distance between vehicles and travelling speeds. However, promising results regarding the maximum delay and the average number of retransmissions foresee important inputs for future services of assisted-driving, in general, and carovertaking assistance, in particular.